Fluorescence optical imaging in patients with active rheumatoid arthritis: a comparison with ultrasound and an association with biomarkers. (4th March 2021) - Kawashiri, S-y; Nishino, A; Shimizu, T; Takatani, A; Umeda, M; Koga, T; Iwamoto, N; Ichinose, K; Tamai, M; Nakamura, H; Origuchi, T; Maeda, T; et al.
Abstract : Objectives : This study compared indocyanine green (ICG)-enhanced fluorescence optical imaging (FOI) and musculoskeletal ultrasound (MSUS), and explored the significance of the FOI findings based on the association between the FOI and MSUS findings and serum biomarkers in patients with rheumatoid arthritis (RA). The study also explored the association between the FOI findings and patients' joint destruction at the joint-area level. Method: We enrolled 50 consecutive patients with active RA from among the patients hospitalized from May 2014 to March 2016 at Nagasaki University Hospital, Japan. FOI images were acquired with the Xiralite ® fluorescence imaging system and compared with the patients' clinical examination results and MSUS findings. On the same day, the patients' clinical disease activity and levels of serum biomarkers (including vascular endothelial growth factor) were obtained. Results: Although the FOI detected synovitis with high sensitivity, the frequency of positive findings and the diagnostic performance with MSUS as the reference standard for FOI differed considerably among the phases of FOI as well as among the affected joint regions. The FOI scores were positively correlated with clinical disease activity, MSUS scores, and serum biomarkers. The severity of FOI-proven synovitis was associated with the presence of MSUS-proven bone erosion. Conclusion: FOI is effective for detecting joint inflammation in RA patients, with high accuracy. The severity of the FOI score was closely associated with the joint destruction at the joint-area level. However, the significance of positive FOI findings differed depending on not only the phase of FOI but also the affected joint regions.